Regioselective Thorpe–Ziegler Cyclization of 3-O-Alkylated Thiophenes; Access to Aminothieno[3,2-b]furans and Aminothieno[3,4-b]furans - Gadais, Charlène; Hesse, Stéphanie; Kirsch, Gilbert (Synthesis, 2012)
A two-step synthesis of polyfunctionalized aminothieno[3,2-b]furans and aminothieno[3,4-b]furans is described and discussed. It was found that O-alkylated thiophenes bearing electron-withdrawing groups in the ortho-position undergo condensation in the presence of an excess of 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU). Furthermore, selective condensation on an ortho-nitrile substituent in preference to ortho-ester or ortho-ketone substituents was observed.
Keywords: thienofurans; thiophenes; O-alkylation; Thorpe–Ziegler; condensation